Efficiency improvement of wastewater treatment plants under the background of “double carbon”: a case study in Jiujiang city, China - Tao, Rufa; Huang, Yuling; Hui, Erqing; Luo, Huihuang; Wang, Dianchang; Lv, Pingyu (Frontiers in Environmental Science, 2024)
Wastewater treatment plants (WWTPs) play a crucial role in modern urban water environmental protection. However, they face challenges related to high operational costs and carbon emissions. This study focused on addressing these issues through an analysis of four urban WWTPs in Jiujiang City, China. The study involved comparing the size and processes of the plants, evaluating influent and effluent water quality, assessing energy consumption and chemical usage, and calculating both direct and indirect carbon emissions. The results demonstrated that the high operational costs and increased carbon emissions in these WWTPs were primarily attributed to low hydraulic loadings, low influent concentration, and high energy and chemical consumption. In response, three targeted scenarios were proposed to enhance the efficiency of the WWTPs and reduce carbon emissions. These scenarios involved adjusting the amount of wastewater imported into the WWTPs to meet the designed capacity, optimizing operating costs, or combining both approaches. Among the scenarios, Scenario 3 emerged as the most effective in terms of improving efficiency and reducing carbon emissions. The operational costs for WWTPs could be reduced in the range of 0.42 to 1.04 RMB/m 3 , representing a reduction rate of 35% to 57%. Additionally, carbon emissions could be lowered from 15.02 to 598.85 gCO2e/m 3 , corresponding to a reduction of 2.91% to 41.38%.While Scenario 2 exhibited a lower carbon emission reduction of 14.8 to 316.33 gCO2e/m 3 , it was identified as the most feasible and easily implementable high-efficiency solution at present, with a reduction in operational costs ranging from 0.43 to 1.31 RMB/m 3 .To achieve zero-energy consumption and zero carbon emissions in wastewater treatment in the future, it is recommended to undertake additional measures, including enhancing dosing system accuracy, implementing tail gas collection, adopting photovoltaic power generation, implementing carbon sequestration techniques, and exploring wastewater heat source recycling. These findings provide valuable insights for optimizing the operational efficiency of urban WWTPs, reducing carbon emissions, and promoting sustainable wastewater treatment practices in Jiujiang City, China.